Transformasi Pembelajaran PAI melalui Praktik Pengembangan Kurikulum di Era Merdeka Belajar - Mita Alisah Tazkiyah; Sunhaji Sunhaji (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
One of the major changes in education during the Merdeka Belajar era is the transformation of education, particularly Islamic religious education. This change highlights the need for curriculum development practices that can create more flexible, contextual, and engaging learning experiences for students. This study aims to analyze the transformation of Islamic Religious Education (PAI) education through curriculum development practices in the Merdeka Belajar era and identify its implications for educational quality. This study uses a qualitative approach with a literature review. Data were collected from various secondary sources, such as academic publications relevant to the years 2021–2025, education policy documents, and journal articles. Data collection was conducted through document analysis, while data analysis was carried out through data reduction, data analysis, interpretation, and conclusions. The results indicate that the transformation of Islamic Religious Education (PAI) education is caused by a shift in the focus of teaching from teachers to students. Curriculum development practices encourage learning flexibility through objectives, strategies, media, and assessments. This indicates that curriculum development plays a crucial role in facilitating more flexible, adaptive PAI education, aligned with the educational goals of the Merdeka Belajar era.